International banking and finance - Lees, Francis A. (New York : Wiley, 1974)
The book is written for the banker and businessman who wishes to obtain a broad picture of what international banking is about, and to understand more clearly how the various aspects of international banking fit together. It is written for the teacher of courses in international finance and investment, international corporate finance, and international banking, who wishes to have a deeper understanding of the organizational approaches, the broad type of lending and investment operations conducted by international banks, and the many financial service areas into which banks have moved. It is also written for the university and special programme student who wishes to dig deeply into an enormously interesting and significant aspect of banking and business.
"A Halsted Press book."
Includes bibliographical references.
rpm 26/04/2018
Loans
Keywords: Banks and banking, International; Foriegn investment; Captital controls; Balance of payment; International finance